PENGARUH PENGGUNAAN PAKAN MAGGOT (Hermetia illucens) TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MAS (Cyprinus carpio) - Hirza Ranggana; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
This study aims to analyze the growth and survival of Goldfish given maggot treatment. The research was carried out in March – May 2022 for the maintenance of biota in private installations and the Proximate Test of Treated Feed was carried out at the Nutrition and Animal Feed Laboratory, Faculty of Animal Husbandry, University Mataram (UNRAM). The research method used a Complete Randomized Design (RAL) by being tested using Analysis of Variance (ANOVA), using four treatments and three repeats, P1 (commercial feed 100%), P2 (wet maggot 100%), P3 (dry maggot 100%), P4 (wet maggot 50% and commercial feed 50%). The results showed that used maggot in all treatments parameters : Absolute weight, specific growth rate, absolute length, feed conversion ratio (FCR), feed utilization efficiency (EPP), survival rate (SR) had an insignificant (P>0.05) influence on the tested research parameters. The conclusions show the use of Commercial feed 100%, wet maggot 100%, dry maggot 100%, and the combination of wet maggot 50% with commercial feed 50% showed the same results in all parameters of the study.